2017
DOI: 10.1070/sm8917
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional collections in surface-like categories

Abstract: Abstract. We provide a categorical framework for recent results of Markus Perling on combinatorics of exceptional collections on numerically rational surfaces. Using it we simplify and generalize some of Perling's results as well as Vial's criterion for existence of a numerical exceptional collection.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Following Hille-Perling [12], Elagin-Lunts [5], Kuznesov [15], etc, the triangulated category D b (coh(F 1 )) ≃ Tr(DG(F 1 )) has a series of full strongly exceptional collections 1 We consider the Morse cohomology degree instead of the Morse homology degree.…”
Section: Homological Mirror Symmetry Of Fmentioning
confidence: 99%
“…Following Hille-Perling [12], Elagin-Lunts [5], Kuznesov [15], etc, the triangulated category D b (coh(F 1 )) ≃ Tr(DG(F 1 )) has a series of full strongly exceptional collections 1 We consider the Morse cohomology degree instead of the Morse homology degree.…”
Section: Homological Mirror Symmetry Of Fmentioning
confidence: 99%
“…The reason for considering these properties is explained in : it can be shown that the action of the Serre functor on the Grothendieck group for all smooth projective surfaces has the extra property that sprefixidnormalΛ has rank precisely 2, whilst the unipotency of the Serre functor holds in complete generality [, Lemma 3.1]. Independently, Kuznetsov developed a similar notion in .…”
Section: Introductionmentioning
confidence: 99%
“…Those properties are described as follows: for a finitely generated free abelian group Λ, a non-degenerate bilinear form −, − : Λ × Λ → Z and an automorphism s ∈ Aut(Λ) we will ask that the extra property that s − id Λ has rank precisely 2, whilst the unipotency of the Serre functor holds in complete generality [14,Lemma 3.1]. Independently, Kuznetsov developed a similar notion in [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When X is a surface, this was proved previously by Vial in [41, Theor. 2.7] by a different method based on delicate properties of exceptional collections on surfaces obtained in recent papers by Perling [34] and Kuznetsov [25].…”
Section: Introductionmentioning
confidence: 99%